Anti-inflammatory effects of phytocannabinoids and terpenes on inflamed Tregs and Th17 cells in vitro - Kyle B.C. Tan; H. Denis Alexander; James Linden; Elaine K. Murray; David S. Gibson (Elsevier, 2024)
Aims: Phytocannabinoids and terpenes from Cannabis sativa have demonstrated limited anti-inflammatory and analgesic effects in several inflammatory conditions. In the current study, we test the hypothesis that phytocannabinoids exert immunomodulatory effects in vitro by decreasing inflammatory cytokine expression and activation. Key methods: CD3/CD28 and lipopolysaccharide activated peripheral blood mononuclear cells (PBMCs) from healthy donors (n = 6) were treated with phytocannabinoid compounds and terpenes in vitro. Flow cytometry was used to determine regulatory T cell (Treg) and T helper 17 (Th17) cell responses to treatments. Cell pellets were harvested for qRT-PCR gene expression analysis of cytokines, cell activation markers, and inflammation-related receptors. Cell culture supernatants were analysed by ELISA to quantify IL-6, TNF-α and IL-10 secretion. Main findings: In an initial screen of 20 μM cannabinoids and terpenes which were coded to blind investigators, cannabigerol (GL4a), caryophyllene oxide (GL5a) and gamma-terpinene (GL6a) significantly reduced cytotoxicity and gene expression levels of IL6, IL10, TNF, TRPV1, CNR1, HTR1A, FOXP3, RORC and NFKΒ1. Tetrahydrocannabinol (GL7a) suppression of T cell activation was associated with downregulation of RORC and NFKΒ1 gene expression and reduced IL-6 (p < 0.0001) and IL10 (p < 0.01) secretion. Cannabidiol (GL1b) significantly suppressed activation of Tregs (p < 0.05) and Th17 cells (p < 0.05) in a follow-on in vitro dose-response study. IL-6 (p < 0.01) and IL-10 (p < 0.01) secretion was significantly reduced with 50 μM cannabidiol. Significance: The study provides the first evidence that cannabidiol and tetrahydrocannabinol suppress extracellular expression of both anti- and pro-inflammatory cytokines in an in vitro PBMC model of inflammation.